2014
DOI: 10.1089/jamp.2013.1070
|View full text |Cite
|
Sign up to set email alerts
|

In VitroComparison of Five Nebulizers During Noninvasive Ventilation: Analysis of Inhaled and Lost Doses

Abstract: In a single-limb circuit bilevel ventilator, vibrating mesh nebulizers positioned between the exhalation port and lung model are more efficient for drug delivery compared with jet or ultrasonic nebulizers. In this position, the improved efficiency of vibrating mesh nebulizers was due to an increase in the inhaled dose and a reduction in the exhaled wasted dose compared with placement between the ventilator and the expiratory port. Because of the high total lost dose, the ultrasonic device should not be recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 58 publications
0
39
1
4
Order By: Relevance
“…Aerosol delivery reported in other studies has also been lower than that found in our study [8, 11, 13], perhaps because of a suboptimal selection of nebulizer location in previous research or because a shorter nebulization time (10 min) was used than the time used in our study (approx. 13 min).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Aerosol delivery reported in other studies has also been lower than that found in our study [8, 11, 13], perhaps because of a suboptimal selection of nebulizer location in previous research or because a shorter nebulization time (10 min) was used than the time used in our study (approx. 13 min).…”
Section: Discussioncontrasting
confidence: 77%
“…Of 5 previous studies [8, 9, 11-13] (Table 1), 1 reported that the proximal position gave higher delivery [9], 2 reported that the distal position had higher delivery [12, 13], and the other 2 studies gave inconsistent results [8, 11]. These discrepancies may be partly explained by differences in the distance between the nebulizer position and the exhalation valve in different studies, as well as the differences in experimental conditions used (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Michotte et al 14 used an adult lung model of NIV with a bi-level ventilator to compare inhaled and lost doses of 5 nebulizers and the influence of nebulizer position. The lung model was set to generate a frequency of 15 breaths/ min.…”
Section: Bench Studiesmentioning
confidence: 99%
“…(3,(12)(13)(14)(15) Recently, some technical issues regarding drug nebulization during NIPPV using a single-limb circuit bilevel ventilator were investigated and resolved with the help of bench studies. (12,14,(16)(17)(18) These studies concluded that the optimal position of the nebulizer device was between the patient and the passive exhalation port. (3,12,14,15,18) Moreover, they showed that vibrating mesh nebulizer devices were more efficient than jet nebulizer devices.…”
Section: Introductionmentioning
confidence: 99%
“…(12,14,(16)(17)(18) These studies concluded that the optimal position of the nebulizer device was between the patient and the passive exhalation port. (3,12,14,15,18) Moreover, they showed that vibrating mesh nebulizer devices were more efficient than jet nebulizer devices. (12,13,18) Although the use of breath-synchronized nebulizers could potentially improve aerosol delivery during NIPPV, (19)(20)(21) this technical aspect has been little studied because breathsynchronized nebulizers are currently not commercially available for use with bilevel ventilators.…”
Section: Introductionmentioning
confidence: 99%